Factors Influencing the Technological Pedagogical Content Knowledge (TPACK) of English Teachers in Primary Schools, Chiang Mai Primary Educational Service Area 1 - Worasiri Boonsue (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this study were to measure the Technological Pedagogical Content Knowledge (TPACK) and to investigate the factors influencing the TPACK of English teachers in primary schools, Chiang Mai Primary Educational Service Area 1. A sample of 81 English teachers in primary schools of Chiang Mai Primary Educational Service Area 1 were selected through two-stage cluster sampling. The research instruments were a likert 5 point scale questionnaire and a semi-structured interview. Data collected by questionnaires were analyzed by frequency, percentage, mean, standard deviation, Pearson Product Moment Correlation Coefficient, and Multiple Regression Analysis. Data from the interview were analyzed through Content Analysis. The results showed that 1) the TPACK of English teachers in primary schools of Chiang Mai Primary Educational Service Area 1 was at a high level (M=3.62 SD=0.55) and 2) the factors influencing the TPACK of English teachers in primary schools, Chiang Mai Primary Educational Service Area 1 at 0.05 level of significant were frequency of technology use in classroom (β = -0.414) and technology literacy (β = 0-.280)